(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to improve initial reading ability by using smart board learning media. The research method applied is quantitative with an experimental approach. The research design used is Single Subject Research (SSR) with an A-B-A pattern. The subject of the study is a deaf student in grade III at SLBN 1 Payakumbuh. The data collection technique involves the use of tests as instruments and data collection tools, namely observation by recording the child’s ability to use the checklist. Data analysis uses graphic visual analysis techniques. The results showed that in the initial baseline phase (A1), which was carried out during three meeting sessions, stable data was obtained at 11%. During the intervention phase (B), which lasted for seven meeting sessions, the stable percentage achieved at the ninth and tenth meetings where for the consonant "s" was 77% and for the consonant "r" was 88%. Furthermore, in the baseline session (A2) there is a stable percentage of 77% for the "s" consonant and 88% for the "r" consonant. Based on the results of the study, it can be concluded that Smart Board learning media can improve early reading skills in deaf children.